2019
DOI: 10.1186/s12872-019-1066-7
|View full text |Cite
|
Sign up to set email alerts
|

Regressed coronary ostial stenosis in a young female with Takayasu arteritis: a case report

Abstract: Background Takayasu arteritis is a rare systemic vasculitis, which affects the aorta and its major branches, especially in young females. Diagnosis and treatment for Takayasu arteritis with coronary stenosis are important to prevent fatal complications. Immunosuppressive treatment such as corticosteroid is a common treatment for this condition. However, the effects of immunosuppressive treatment on inflammatory coronary stenosis caused by Takayasu arteritis remains unknown. Case pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Extremely thickened adventitia with fibrosis involving the myocardium and the epicardial nerve plexus was also observed (b) second intervention revealed an accumulation of inflammatory cells with granulomas in a small section. A previous study reported the usefulness of 18F-fluorodeoxyglucosepositron emission tomography for diagnosing coronary Takayasu arteritis [12], which possibly could have helped diagnosis before coronary bypass surgery in the present case.…”
Section: Discussionmentioning
confidence: 66%
“…Extremely thickened adventitia with fibrosis involving the myocardium and the epicardial nerve plexus was also observed (b) second intervention revealed an accumulation of inflammatory cells with granulomas in a small section. A previous study reported the usefulness of 18F-fluorodeoxyglucosepositron emission tomography for diagnosing coronary Takayasu arteritis [12], which possibly could have helped diagnosis before coronary bypass surgery in the present case.…”
Section: Discussionmentioning
confidence: 66%
“…In our case, TA was well controlled by the combination of prednisolone and TCZ, and coronary artery stenosis showed slight regression after the administration of these drugs. In an 18-year-old woman with TA who had severe stenosis in the ostium of both the left main trunk and the LAD, 4 months of combined immunosuppressive treatment with corticosteroid and TCZ resulted in a regression of the coronary ostial stenosis (35). Pan et al demonstrated that six-month treatment with tocilizumab improved the degree of lumen stenosis in most lesions of the coronary arteries in patients with TA (36).…”
Section: Discussionmentioning
confidence: 99%
“…Mohan et al reported reduced stenotic lesions of the coronary ostia by steroid treatment in an 11-year-old boy with the aid of cardiac-gated computed tomography [ 18 ]. Tetsuro et al reported attenuated coronary ostial stenosis via coronary angiography with immunosuppressive combination therapies [ 19 ]. As described in our case, an increased EEM area of the ostium of the LMCA was observed by longitudinal evaluation of IVUS at different time points after PTCA and immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%